Suspended Collagen Hydrogels to Replicate Human Colonic Epithelial Cell Interactions with Immune Cells. Issue 11 (30th June 2022) - Hinman, Samuel S.; Massaro, Angelo; Wang, Yuli; Sims, Christopher E.; Kim, Raehyun; Allbritton, Nancy L.
Abstract: The human colon plays a critical role in fluid and salt absorption and harbors the largest immune compartment. There is a widespread need for in vitro models of human colon physiology with its innate immune system. A method is described to produce a cassette with a network of struts supporting a suspended, non‐chemically cross‐linked collagen hydrogel scaffold compatible with the co‐culture of primary gastrointestinal epithelium and migratory inflammatory cells. The epithelial monolayer cultured on the suspended collagen possesses a population of polarized and differentiated cells similar to that present in vivo. This epithelial layer displays proper barrier function with a transepithelial electrical resistance (TEER) ≥ 1, 500 Ω cm 2 and an apparent permeability ≤10 −5 cm 2 s −1 . Immune cells plated on the basal face of the scaffold transmigrated over a period of 24 h to the epithelial layer in response to epithelial production of IL‐8 induced by luminal stimulation of Clostridium difficile Toxin A. These studies demonstrate that this in vitro platform possesses a functional primary colonic epithelial layer with an immune cell compartment capable of recruitment in response to pro‐inflammatory cues coming from the epithelium. Abstract : A primary human colonic epithelial layer is formed on a collagen hydrogel suspended on a framework of polyester struts. The hydrogel supports an immune cell compartment capable of responding to pro‐inflammatory cues from the epithelium by migration through the hydrogel to interface with the epithelial cells. This platform enables studies of the human colonic epithelium and intestinal immune compartment interface.